Online Gambling and Economic Crisis: Safeguarding National Stability through Islamic Economics - Sarehan Khawankawin; Muhamad Rahman Bayumi; Rizal Alfit Jaya; Muhammad Fikri Hijami (Institut Agama Islam Negeri (IAIN) Curup, 2025)
ABSTRACT Purpose: This study aims to analyze the behavior of the online gambling phenomenon that disrupts the stability of the national economy. Design/Method/Approach: The research method uses a qualitative approach with a focus on the phenomenology of online gambling behavior. Data were collected through in-depth interviews with victims affected by online gambling, as well as document analysis from relevant sources. Semi-structured interviews were conducted to understand personal experiences, perceptions, and the impact of online gambling behavior on victims’ lives. The stages in this research include understanding the data, developing codes, and ultimately identifying themes. Data analysis was carried out using thematic analysis techniques with NVIVO12 to identify patterns and themes that emerged from the collected data. Findings: The findings of this study reveal that online gambling behavior has disrupted and damaged the foundations of the economic system. In the long run, such practices undermine Indonesia’s economic stability and contradict the principles of Islamic economics, which emphasize justice, sustainability, and the prevention of harm (mafsadah) to society. Originality/Values: Online gambling has become one of the urgent problems in Indonesia. This issue is reinforced by the wave of digitalization, which provides many conveniences for the public in accessing online gambling. The rise of online gambling problems causes Indonesia’s economy to continually face issues such as poverty, wage inequality, and low productivity, which can generate a multiplier effect on other sectors.